Mediating effect of firm efficiency on the controlling shareholdings–firm performance nexus: Evidence from public listed firms in Malaysia - Ting, Irene Wei Kiong; Asif, Jawad; Kweh, Qian Long; Phuong, Tran Thi Kim (Springer Science and Business Media Deutschland GmbH, 2024)
This study examines how controlling shareholders influence firm performance through the mediating role of firm efficiency in transforming inputs into outputs. To achieve this objective, it conducts a mediation analysis with 5,000 bootstraps on a dataset of 2,849 firm-year observations of publicly listed firms in Malaysia from 2009 to 2019. The findings reveal a positive relationship between controlling shareholdings and firm performance, with both total and indirect effects having this positive relationship. Moreover, while controlling shareholdings improve firm performance, firm efficiency partially mediates this relationship. Thus, improved firm efficiency plays a critical role in understanding the relationship between governance by controlling shareholders and enhanced firm performance. In summary, this study contributes to the existing literature by expanding our understanding of the complex relationship between controlling shareholdings, firm efficiency, and firm performance. In addition, the findings shed light on the importance of indirect channels in shaping organizational outcomes. As such, this study provides a valuable direction for future research in this area.